Bioaffinity-based surface immobilization of antibodies to capture endothelial colony-forming cells - Boulanger, Mariève D.; Level, Hugo A.; Elkhodiry, Mohamed A.; Bashth, Omar S.; Chevallier, Pascale; Laroche, Gaétan; Hoesli, Corinne A. (PLOS ONE, 2022)
Maximizing the re-endothelialization of vascular implants such as prostheses or stents has the potential to significantly improve their long-term performance. Endothelial progenitor cell capture stents with surface-immobilized antibodies show significantly improved endothelialization in the clinic. However, most current antibody-based stent surface modification strategies rely on antibody adsorption or direct conjugation via amino or carboxyl groups which leads to poor control over antibody surface concentration and/or molecular orientation, and ultimately bioavailability for cell capture. Here, we assess the utility of a bioaffinity-based surface modification strategy to immobilize antibodies targeting endothelial cell surface antigens. A cysteine-tagged truncated protein G polypeptide containing three Fc-binding domains was conjugated onto aminated polystyrene substrates via a bi-functional linking arm, followed by antibody immobilization. Different IgG antibodies were successfully immobilized on the protein G-modified surfaces. Covalent grafting of the protein G polypeptide was more effective than surface adsorption in immobilizing antibodies at high density based on fluorophore-labeled secondary antibody detection, as well as endothelial colony-forming cell capture through anti-CD144 antibodies. This work presents a potential avenue for enhancing the performance of cell capture strategies by using covalent grafting of protein G polypeptides to immobilize IgG antibodies.